Purification and physicochemical properties of a ribonuclease produced by Aspergillus flavipes (IZ:1501) - Gomes, Eleni [UNESP]; Serzedello, Alcides [UNESP]; Da Silva, Roberto [UNESP] (My University, 1998)
A RNase of Aspergillus flavlpes (IZ:1501) was purified from culture medium by chromatography on DEAE-cellulose and Sephadex G50 columns, after 96 h of cultivation. The molecular weight of the RNase was estimated to be 15 kD by gel filtration using Sephadex G100, and the optimum pH and temperature were 4.0 and 55°C, respectively. Catalytic activity was inhibited by Hg2+, Ag+, Fe3+, Co2+ and Zn2+. The enzyme showed guanosine specificity producing only 3′-GMP from yeast RNA.
Keywords: Aspergillus; Nucleotides; Ribonuclease